Immunohistochemical studies of protein kinase D (PKD) 2 expression in malignant human lymph - Shlapatska, L.M.; Sidorenko, S.P.; Yurchenko, O.V.; Berdova, G.G.; Mikhalap, S.V.; Lint J. Van; Kovalevska, L.M. (Experimental Oncology, 2006)
Aim: To study the PKD2 expression, autophosphorylation and localization in reactive lymph nodes and tumors of lymphoid tissues. Materials and Methods: Specific antibodies, which recognize PKD1/2 or PKD2 and autophosphorylated PKD1/2, were used for immunohistochemical and biochemical studies of tonsils, reactive lymph nodes, tumor samples of non-Hodgkin’s lymphoma (NHL) and Hodgkin’s lymphoma (HL). Results: Immunohistochemical and biochemical analysis of PKD1 and PKD2 expression showed PKD2 expression in tonsils, reactive lymph nodes and tumor tissues from patients with NHL and HL. Furthermore, we were not able to reveal PKD1 expression in studied lymphoid tissues. In tonsils and reactive lymph nodes the PKD2 expression was detected in T and B cell zones with highest level in germinal centers of lymphoid follicles and the maximum level of autophosphorylation in the light zones of the germinal centers. We found that low level of PKD2 expression and autophosphorylation was characteristic feature for mantle cell lymphomas, Burkitt’s lymphomas, and in 50% of CLL/small lymphocytic lymphomas. Lymphoma cells of germinal center origin and with activated B cell phenotype (diffuse large B cell lymphomas, HL) and anaplastic large cells lymphoma demonstrated the high level of PKD2 expression and autophosphorylation. Conclusions: The level of PKD2 expression and autophosphorylation in neoplastic cells corresponds to the expression pattern of this kinase in their normal analogs, and to the level of cell differentiation and activation. Цель: изучить экспрессию, аутофосфорилирование и локализацию PKD2 в клетках реактивно измененных лимфaтических
узлов и опухолях лимфоидной ткани. Материалы и методы: специфические антитела, распознающие PKD1/2 или PKD2
и аутофосфорилированную PKD1/2, были использованы для иммуногистохимического и биохимического анализа клеток
небных миндалин, реактивно измененных лимфaтических узлов, биоптатов опухолей у больных неходжкинскими злокачественными
лимфомами (НХЛ) и лимфомой Ходжкина (ЛХ). Результаты: при иммуногистохимическом и биохимическом
исследовании выявлена экспрессия PKD2 в клетках миндалин, гиперплазированных лимфатических узлов и различных
гистологических форм НХЛ и ЛХ. Экспрессия PKD1 в изученных нами лимфоидных тканях выявлена не была. Экспрессия
PKD2 была выявлена в T- и B-клеточных зонах миндалин и реактивно измененных лимфатических узлов. Наиболее
высокий уровень экспрессии отмечался в клетках зародышевых центров лимфоидных фолликулов, максимальный уровень
аутофосфорилирования — в светлых зонах зародышевых центров. Обнаружено, что низкий уровень экспрессии и аутофосфорилирования
PKD2 является характерной особенностью лимфом из клеток мантийной зоны, лимфомы Беркитта,
в 50% случаях лимфом из малых лимфоцитов/ХЛЛ. Клетки лимфом, возникающих из клеток зародышевых центров с
фенотипом активированных B-клеток (диффузная лимфома из крупных B-клеток, ЛХ), а также анапластическая крупноклеточная
лимфома характеризовались высоким уровнем экспрессии и аутофосфорилирования PKD2. Выводы: уровень
экспрессии и аутофосфорилирования PKD2 в клетках новообразований соответствует особенностям экспрессии этих
киназ в соответствующих нормальных аналогах, уровню клеточной дифференцировки клеток и их активации.